Learning Maharah Qira’ah Using the Book “Cara Cepat Bisa Baca Kitab Metode 33” - Aini, Qurrotul; Mu’at, Mu’at (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
Purpose – This study aims to describe the characteristics of learning maharah qira’ah using the book Cara Cepat Bisa Baca Kitab Metode 33, which is implemented at the Al-Hasyim Islamic Boarding School in Mayangan, Jogoroto, Jombang. Design/Methodology/Approach – This study uses a qualitative approach with a case study design. The research was conducted at Al-Hasyim Islamic Boarding School in Mayangan, Jogoroto, Jombang. Data were collected through observation, interviews, and documentation. Data analysis was carried out qualitatively using data reduction, data presentation, and conclusion drawing techniques. Findings – Learning maharah qira’ah using the book Cara Cepat Bisa Baca Kitab Metode 33 combines linguistic tools (namely nahwu and sharaf) with reading practice. Knowledge of nahwu and sharaf rules serves as a foundational provision for students in reading and understanding the meaning of Arabic texts. This learning is conducted during the morning diniyah activities in the wustho class every day. The learning process consists of three stages: opening activities, core activities, and closing activities. The core activities follow the systematic approach of the book, which includes vocabulary (mufrodat), grammatical rules, and exercises. Research Limitations/Implications – The limitations of this study lie in its scope, which is confined to Al-Hasyim Islamic Boarding School and thus cannot be generalized to other institutions. In addition, the short duration of the study means that the long-term implementation and effectiveness of the Cara Cepat Bisa Baca Kitab Metode 33 book are not yet fully understood.